RUKUN NIKAH DALAM PERSPEKTIF MAZHAB SYAFI’I: ANALISIS ISTINBATH HUKUM DALAM KITAB FATHUL MUIN - Dairobi, Ahmad Habib; Amar Adly, Muhammad (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
The pillars of marriage are fundamental elements that determine the validity of a marriage contract in Islamic law. Differences in emphasis between Islamic jurisprudence schools on the pillars and conditions of marriage indicate the diversity of legal istinbāṭ methods used by scholars. This article aims to analyze the concept of the pillars of marriage from the perspective of the Shafi’i school of thought through the legal istinbaṭ approach contained in the book Fathul Mu’in by Sheikh Zainuddin bin Abdul Aziz Al-Malibari. This study uses a qualitative research method with a normative-juridical approach and library research, with the main data source being the book Fathul Mu’in and supported by other Shafi’iyyah fiqh books and relevant Islamic legal literature. The results of the study indicate that the Shafi’i school of thought establishes five pillars of marriage, namely the prospective husband, prospective wife, guardian, two witnesses, and sighat ijab qabul. The determination of these pillars is based on the evidence of the Qur’an, the hadith of the Prophet Muhammad SAW, the consensus of scholars, and qiyas processed through a systematic and strict legal istinbaṭ method. The book Fathul Mu’in consistently emphasizes the importance of fulfilling all the pillars of marriage as an absolute requirement for the validity of the marriage contract, while also providing a detailed explanation of the legal consequences if one of these pillars is not fulfilled. This study is expected to provide an academic contribution in enriching the treasure trove of Islamic family law studies, especially in understanding the legal construction of the pillars of marriage according to the Shafi’i school of thought and its relevance in contemporary Muslim marriage practices.